2012
DOI: 10.4048/jbc.2012.15.4.434
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Surgery and Phase of the Menstrual Cycle Affects Survival in Breast Cancer

Abstract: PurposeThe impact of time of surgery based on the menstrual cycle is a controversial issue. Two decades after the first interest in this topic, a number of studies with conflicting results have not helped to resolve this problem. This study aimed to prospectively evaluate the impact of timing of surgery based on the menstrual cycle on survival rates of breast cancer patients, and various clinical and hormonal classifications of the menstrual cycle were compared in order to determine the phase of the menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For this reason, women prescribed antidepressants such as fluoxetine require a lower dose while taking oral contraceptives because higher doses result in drug accumulation in the body (Damoiseaux et al, ). Menstrual cycle phase may be an important consideration for treating breast cancer; survival after curative surgery is most effective in the luteal phase of the menstrual cycle (Kucuk and Atalay, ). Manipulation of ovarian hormones, such as ovarian hormone withdrawal from hormones simulated pregnancy, can also be used to induce depressive‐like phenotypes in female rats (Galea et al, ).…”
Section: Studying Women (And Men): Influence Of Puberty Aging and Rmentioning
confidence: 99%
“…For this reason, women prescribed antidepressants such as fluoxetine require a lower dose while taking oral contraceptives because higher doses result in drug accumulation in the body (Damoiseaux et al, ). Menstrual cycle phase may be an important consideration for treating breast cancer; survival after curative surgery is most effective in the luteal phase of the menstrual cycle (Kucuk and Atalay, ). Manipulation of ovarian hormones, such as ovarian hormone withdrawal from hormones simulated pregnancy, can also be used to induce depressive‐like phenotypes in female rats (Galea et al, ).…”
Section: Studying Women (And Men): Influence Of Puberty Aging and Rmentioning
confidence: 99%
“…Differences in classification methods can introduce significant variability into results, and may provide some explanation for the differences in results between different studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)26,27) (Table I). Other factors include inaccuracies in menstrual cycle data, as there can be significant variability in cycle length (i.e., 22-36 days) between women (35); and other factors, such as irregular menses, use of oral contraceptives, recent pregnancies, or differing hormonal and chemotherapy treatment regimens may impact circulating ovarian hormones and menstrual cycle phase.…”
Section: Confounding Factors That Could Affect the Relationship Betwementioning
confidence: 99%
“…Mouse studies supported by small retrospective clinical studies suggested that changes in the characteristics of the tumour and tumour microenvironment across the menstrual cycle might influence the metastatic potential of tumour cells, and affect clinical outcomes in premenopausal women. However, while some studies suggest that surgery performed during the luteal phase results in favourable outcomes in terms of metastatic incidence, disease free survival, and overall survival (6)(7)(8)(9)(10)(11)(12)(13)(14), other studies report the follicular phase is more favourable (5,15,16), and other studies show no association (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a systematic review and meta-analysis found the literature on the matter to be inconclusive, but noted that the studies supporting the benefits of surgery in the luteal phase were generally more robust, with larger cohorts and longer follow-up times [52]. One such prospective study reported decreased DFS when surgeries were scheduled in the follicular phase of the menstrual cycle [53]. This effect was independent of the hormone receptor status of the tumors, indicating that the effect was not due to an intrinsic susceptibility of the tumors themselves to fluctuating hormone levels.…”
Section: Plos Onementioning
confidence: 99%